Machine Learning Algorithms Based Network packets Cataloguing - Balaji Karumanchi (International Journal of Advanced Science and Technology, 2020)
The proposed system enables in capturing the packets and determines which attack was launched with the assist of analysis in a given network. Machine learning based algorithms are used to distinguish between harmful and harmless packets. The traditional methods followed a tool-based analysis. In the proposed system, machine learning based algorithms are used which is based on artificial intelligent to prepare the system to give an accurate outcome. To educate the system, KDDCUP 99 is used which contains lots of features to recognize various network attacks Keywords: Machine Learning, packet classification, Packet analysis, Data Mining, Network attacks, Security, KDD data set